1202Examining the mental health effect of caring among adolescents using augmented inverse probability treatment weighting. (2nd September 2021) - King, Tania; Singh, Ankur; Disney, George
Abstract: Background: Caring exerts significant impacts on the lives of those providing care, however there has been limited quantitative analysis of the mental health impacts on young carers. This research aimed to estimate the effect of informal caring at age 14/15 years on mental health at age 18/19 years. Methods: Data was drawn from Waves 5, 6, 8 (2012-2018) of the Longitudinal Study of Australian Children. Effects of caring on mental health were assessed using augmented inverse probability treatment weighting, with adjustment for potential confounders. Caring was assessed with both a binary (any caring vs none), and a three-category variable (no caring, less than daily caring, daily caring). Results: In complete case models, binary caring at age 14/15 years was associated with poorer mental health at age 18/19 years, with an average treatment effect (ATE) of 1.10 (95%CI 0.37, 1.83). The ATE of daily caring compared to no caring at age 14/15 years of age was 1.94 (95%CI 0.48, 3.39), and caring less than daily (compared to no caring) was associated with a treatment effect of 0.83(95%CI 0.06, 1.61). Associations were robust to several sensitivity analyses. Conclusions: These results suggest there is a mental health impact of caring in adolescence on mental health four years later. Key messages: These results highlight the need for support for young carers. Such support is particularly essential for those providing more intensive caring.